Biuletyn Informacyjny . aktualności życia publicznego, no. 2a, 1976 - ed. by Ed. Committee (s.n.], 1976)
Creation and circulation: First issues typewritten and carbon-copied by various persons, also in fragments, there exist xerox copies of the typescript.